Peran Orang Tua dalam Memotivasi Belajar Anak pada Pembelajaran Daring di Desa Gemiring Lor - Novy Zuliana Sari; Erik Aditia Ismaya; Muhammad Noor Ahsin (PGSD Universitas Muria Kudus, 2022)
The purpose of this study is to describe the role of parents in motivating children's learning in online learning in Gemiring Lor Village.The research method used is qualitative with a descriptive approach. Data collection is done by observation, in-depth interviews, documentation, recording. The research was conducted in Gemmiring Lor Village. The object of research is the role of parents in motivating children's learning in online learning for children who are in grade IV and the informants are grade IV students, totaling 3 and their parents. The data analysis used is that there are three lines of qualitative data analysis, namely data reduction, data presentation, and drawing conclusions.The results showed that the role of people in increasing children's learning motivation during online learning during the pandemic by providing encouragement, mentoring for learning, and giving time to play first after that if it was time to study children had to learn to complete the tasks given by the teacher. In addition, giving rewards or prizes so that children have a desire to learn.